Investigation of biodegradable metal for Urological Applications (2020)
Temporary medical implants made of degradable metals have been studied due to their safely dissolving in the human body. Zinc based alloys are the alternative to overcome the limitations of magnesium and iron samples in physiological environment. In this study, the characterisation of mechanical properties, determination of the degradation resistance in artificial urine (AU) for electrochemical and immersion tests, and analysis of the elemental composition of the corrosion layer were carried out in pure Zn samples (wire and sheet). The corrosion rates obtained were affected by the presence of the ZnO. Non-uniform corrosion of Zn was observed and Ca in the corrosion layer is an undesirable result. Moreover, the diameter reduction for Zn wire samples displayed a relationship between mass loss and immersion time. This work shows significant results to take account in further studies in the urological field; however, mechanical properties and corrosion behaviour of pure Zn samples need to be improved.